Supporting school teachers’ rapid engagement with online education - Abaci, Serdar (Educ Technol Res Dev, 2020)
In response to Philipsen et al.'s (Educ Technol Res Dev 67:1145–1174, 2019) article titled “Improving teacher professional development [TPD] for online and blended learning [OBL]: a systematic meta-aggregative review”, we apply their proposed framework of important components of TPD for OBL to the support we provided to primary and secondary teachers as they engaged with online education during the COVID-19 pandemic. We reflect on observations of particular challenges for school teachers and the reasons behind them. While this framework is a useful reflection tool to guide professional learning for teachers beyond the emergency situations, we found that it is biased towards TPD for OBL in higher education settings. Thus, we suggest future work to differentiate educational levels in order to account for operational differences.